Coordination, Commitment, and Enforcement: The Case of the Merchant Guild - Greif, Avner; Milgrom, Paul; Weingast, Barry R. (Journal of Political Economy, 1994)
The authors interpret historical evidence in light of a repeated-game model to conclude that merchant guilds emerged during the late medieval period to allow rulers of trade centers to commit to the security of alien merchants. The merchant guild developed the theoretically required attributes, secured merchants' property rights, and evolved in response to crises to extend the range of its effectiveness, contributing to the expansion of trade during the late medieval period. The authors elaborate on the relations between their theory and the monopoly theory of merchant guilds and contrast it with repeated-game theories that provide no role for formal organization. Copyright 1994 by University of Chicago Press.